COMPORTAMIENTO ESPACIAL DE TRIPS (INSECTA: THYSANOPTERA), EN PLANTACIONES COMERCIALES DE AGUACATE (PERSEA AMERICANA MILL.) EN ZITÁCUARO, MICHOACÁN, MÉXICO - Ramírez Dávila, José Francisco; Solares Alonso, Víctor Manuel; Figueroa Figueroa, Dulce Karen; Sánchez Pale, Jesús Ricardo (Instituto de Ecología, A.C., 2013)
Mexico is the largest producer and exporter of avocados in the world. Thrips are considered a major pest of avocados in Mexico, because of their association with the disease called fruitscab, caused by the fungus (Elsinoe perseae). This disease represents a serious constraint to crop production; the fungus penetrates the fruit through injuries caused by a complex of several species of thrips. The analysis of the spatial behavior of this pest should provide information that will help establish appropriate management strategies, directed in avocado orchards. This work aimed to determine the spatial distribution of populations of thrips in avocado (Persea americana Mill) Cv. Hass. using spatial statistical (Geostatistics and SADIE) that would lead in the case of Geostatisticsto generate maps by kriging. The short term spatial and temporal stability of thrips populations was established.The results showed that thrips populations have an aggregate distribution, adjusting to Spherical and Gaussian type models. Such behavior was corroborated by SADIE indices and the density maps produced. The results demonstrate that there is an infestation of 100% in the study plots, which is of great interest to direct control measures on specific areas of infestation and thereby achieve economic and environmental savings.